METHODOLOGY OF TEACHING OPTICS USING A COLLABORATIVE APPROACH (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This paper explores the methodology of teaching optics through a collaborative learning approach. Collaborative teaching emphasizes active student participation, peer interaction, and shared responsibility for learning, which are particularly effective in mastering abstract and mathematically intensive topics in optics. The methodology integrates group-based problem solving, experimental activities, discussion-driven concept formation, and project-oriented tasks that encourage critical thinking and conceptual understanding. Special attention is given to the role of the teacher as a facilitator who guides learning rather than delivering information in a traditional lecture format. The proposed approach enhances students’ motivation, communication skills, and ability to apply theoretical knowledge to practical optical phenomena. The annotation also highlights the effectiveness of collaborative learning in developing scientific reasoning, improving academic performance, and fostering teamwork skills. The methodology can be successfully implemented in secondary and higher education institutions and is adaptable to modern educational technologies and laboratory-based instruction in physics.